(7a+4)(8a+3)=

Simple and best practice solution for (7a+4)(8a+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7a+4)(8a+3)= equation:


Simplifying
(7a + 4)(8a + 3) = 0

Reorder the terms:
(4 + 7a)(8a + 3) = 0

Reorder the terms:
(4 + 7a)(3 + 8a) = 0

Multiply (4 + 7a) * (3 + 8a)
(4(3 + 8a) + 7a * (3 + 8a)) = 0
((3 * 4 + 8a * 4) + 7a * (3 + 8a)) = 0
((12 + 32a) + 7a * (3 + 8a)) = 0
(12 + 32a + (3 * 7a + 8a * 7a)) = 0
(12 + 32a + (21a + 56a2)) = 0

Combine like terms: 32a + 21a = 53a
(12 + 53a + 56a2) = 0

Solving
12 + 53a + 56a2 = 0

Solving for variable 'a'.

Factor a trinomial.
(4 + 7a)(3 + 8a) = 0

Subproblem 1

Set the factor '(4 + 7a)' equal to zero and attempt to solve: Simplifying 4 + 7a = 0 Solving 4 + 7a = 0 Move all terms containing a to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 7a = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 7a = 0 + -4 7a = 0 + -4 Combine like terms: 0 + -4 = -4 7a = -4 Divide each side by '7'. a = -0.5714285714 Simplifying a = -0.5714285714

Subproblem 2

Set the factor '(3 + 8a)' equal to zero and attempt to solve: Simplifying 3 + 8a = 0 Solving 3 + 8a = 0 Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 8a = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 8a = 0 + -3 8a = 0 + -3 Combine like terms: 0 + -3 = -3 8a = -3 Divide each side by '8'. a = -0.375 Simplifying a = -0.375

Solution

a = {-0.5714285714, -0.375}

See similar equations:

| .5k+6g=2k | | z/5-4=1/5/6 | | 0.23= | | 17/13=x/10 | | -7(-3b+11)+9(-2-3b)-(-5b-8)=-37 | | x-36=44.9 | | x/4-5=7/8 | | 0.217/7 | | 5x+10(x+3)=15 | | 3/6z-6 | | 5x+4y^2= | | 41+2n=2+n | | x^2(x-2)+7x(2-x)-10(2-x)= | | -x(x-3)+x(-2x-8)= | | x^3+15x^2+6x+1=0 | | 9x3/2 | | 9(2+t)-7(t+1)= | | Y=28x-2xsquared | | 5h+6(2h+10)=10 | | 3x-2(5x-y)-(4y+x)= | | w^2(w-3)=350 | | 5x-22=26+x | | Y^2-2y= | | 3.4+z=-7 | | -6th-7=17 | | 1/3x-1/7=8 | | x^2+38x+361=36 | | 5xy-3y+10x-6= | | x-2(x+1)=5+9 | | 15/2x+4=-2 | | 12t=16 | | 2x^2+xy-y^2=2 |

Equations solver categories